2021
DOI: 10.3390/su132111942
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and the New Normal of Organizations and Employees: An Overview

Abstract: The COVID-19 pandemic has hit organizations and employees in every sector worldwide in unprecedented ways. It became extremely difficult for organizations and employees across sectors to operate under increased mobility restrictions. The pandemic effectively disrupted previous operational models and imbued changes such as telework and digital adoption that are pervasive and may potentially last beyond the pandemic. Amid these circumstances, it was essential to ask how organizations and employees will sustain t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 142 publications
(178 reference statements)
0
53
0
9
Order By: Relevance
“…It showed that organizations can work differently from how they used to and that various tasks can be fulfilled digitally. Raghavan et al, notice that, "although these trends vary across sectors and within and across countries, there is an overall increase in the flexibility of organizations and employees in adopting new solutions, making them more open to innovation" [3]. By implementing open innovation (OI) approaches, manufacturing companies can improve their collaboration process throughout the whole supply chain, minimize production waste, ensure better working conditions, and adapt business models [2].…”
Section: Introductionmentioning
confidence: 99%
“…It showed that organizations can work differently from how they used to and that various tasks can be fulfilled digitally. Raghavan et al, notice that, "although these trends vary across sectors and within and across countries, there is an overall increase in the flexibility of organizations and employees in adopting new solutions, making them more open to innovation" [3]. By implementing open innovation (OI) approaches, manufacturing companies can improve their collaboration process throughout the whole supply chain, minimize production waste, ensure better working conditions, and adapt business models [2].…”
Section: Introductionmentioning
confidence: 99%
“…The Sustainable Development Goals (SDG) themselves include digital competence as a key aspect in the 2030 Agenda. In addition, the implementation of digital transformation plans at the mesolevel will ensure the sustainability of organizations and jobs in the new normal [10]. Digital devices, the Internet, and e-learning platforms are essential to the learning, communication, and expression of university students.…”
Section: New Learning Spaces and Ictmentioning
confidence: 99%
“…Overall, what matters most for organizations is employees' well-being (9,(59)(60)(61)(62). Investigating the effects of COVID-19 on organizations and employees, Raghavan et al (63) find that telework and digital adoptions are two trends in COVID-19. They provide four recommendations to organizations: "improve remote work infrastructure for employees, " "use digital tools to improve communication and workflow within organizations, " "Deploy additional resources at the organizational level for digital transformation, " and "Collaborate with technology firms and academic institutions to enhance the digital skills of employees and overcome the digital divide."…”
Section: Role Of Psis In Covid-19 Managementmentioning
confidence: 99%